Identifying nanotechnological linkages in the Finnish economy - Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2007)
Nanotechnology, as an emerging science-based technology, is seen to have great potential both in scientific as well as economic terms. In this paper the focus is on identifying the technological linkages between the Finnish nanotechnology community and the industrial incumbents. These technological link-ages are first observed at a broader level in comparison with the technological strengths of the Finnish industries, and then in greater detail at the level of companies. In addition, the absorptive capacity of the incumbents is discussed to illustrate their ability to take advantage of external sources of knowledge. The descriptive analysis shows that the R&D activities of the Finnish nano-community are linked up to the technological specialisation of Finnish industry in broader sense and that there are potential technological linkages to various industrial sectors. Further, the nano-related incumbents are characterised by a higher level of absorptive capacity. The conclusion is that nanotechnology is connected to traditional and `high-tech' industries. The nano-related incumbents might also exhibit an ability to utilise external sources of knowledge, and can possibly provide commercialisation paths for the smaller nano-dedicated companies. The future will tell whether the incumbent companies will play a key role in the commercialisation of nanotechnology in Finland..
Keywords: O33; O30; 330; nanotechnology; Finland; general purpose technology; technology life cycle; absorptive capacity; Nanotechnologie; Betriebliche Forschung; Technischer Fortschritt; Innovationsdiffusion; Kommerzialisierung; Finnland